PENGEMBANGAN ORGANISASI FORUM KOORDINASI PIMPINAN DAERAH DALAM MENUNJANG PELAKSANAAN TUGAS DAN FUNGSI PENYELENGGARAAN URUSAN PEMERINTAHAN UMUM - I Dewa Made Wiratma; Fernandes Simangunsong (Governance, 2023)
This study aims to determine and analyze the Organizational Development of the Regional Leadership Coordination Forum in supporting the implementation of the duties and functions of administering general government affairs, to identify and analyze the supporting and inhibiting factors for the Organizational Development of the Regional Leadership Coordination Forum in supporting the implementation of the duties and functions of implementing general government affairs, to identify and analyze efforts to overcome the inhibiting factors for Regional Leadership Coordination Forum Organizational Development in supporting the implementation of the duties and functions of implementing General Government Affairs in Bolaang Mongondow Regency, North Sulawesi Province. This research is a qualitative research using an inductive approach. The research method used in the form of observation, documentation and interviews. Based on the results of field analysis, it can be concluded that development has not yet occurred in the Bolaang Mongondow Regency Regional Leadership Coordination Forum, North Sulawesi Province, but the implementation of the duties and functions of implementing general government affairs is still being carried out. In the development process, the existing inhibiting factors are not a problem in the Organizational Development of the Regional Leadership Coordination Forum in Bolaang Mongondow Regency.